2022
DOI: 10.1021/acs.jpcb.2c06415
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Solvation Structure of Li-Ion Battery Electrolytes Using DFT-Based Computation and 1H NMR Spectroscopy

Abstract: Molecular dynamics (MD) simulations, density functional theory (DFT) calculations, and 1H NMR spectroscopy were performed to gain a complementary understanding of the concentrated Li-ion electrolyte system, lithium bis(trifluoro­methane­sulfonyl)imide (Li[TFSI]) dissolved in tetraglyme. The computational methods provided the concentration dependence of differing solvation structure motifs by reference to changes in the corresponding NMR spectra. By combining both the computational and experimental methodologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…This indicates that the lifetime of bG is longer than the ∼120 ps duration of the individual AIMD trajectories, an observation consistent with many earlier classical MD studies, where the residence times of Li + in glymes and PEOs were found to be in the range of 1−1000 ns. [27][28][29][30][31]33,34,38 These long lifetimes allow us to treat bG and uG as two different species and compute their autocorrelations and cross-correlations unambiguously within the simulation time scale. In addition, the fact that bG structures are relatively rigid enables analysis of its GNMs.…”
Section: Dihedral Angle Distribution Of Diglyme Molecules Inmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that the lifetime of bG is longer than the ∼120 ps duration of the individual AIMD trajectories, an observation consistent with many earlier classical MD studies, where the residence times of Li + in glymes and PEOs were found to be in the range of 1−1000 ns. [27][28][29][30][31]33,34,38 These long lifetimes allow us to treat bG and uG as two different species and compute their autocorrelations and cross-correlations unambiguously within the simulation time scale. In addition, the fact that bG structures are relatively rigid enables analysis of its GNMs.…”
Section: Dihedral Angle Distribution Of Diglyme Molecules Inmentioning
confidence: 99%
“…23−38 Li + solvation structure as well as transport and related dynamics, which require prolonged simulations, were studied mainly using classical MD. 24,25,[27][28][29][30][31][32][33][34][35]38 Ab initio MD (AIMD) was also employed in recent study of Li + solvation structure in glymes 36,37 and in the analysis of Li + transport along a single PEO chain. 26 Various properties of Li + solvates, such as coordination structure, glyme backbone conformations, and normal mode vibrations at local energy minima, have also been analyzed with ab initio methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations